‘Memória e oralidade: a identidade do leite condensado Moça a partir de uma perspectiva discursiva’ - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The present work is a bibliographic research with exploratory and hermeneutic nature, which analyses the strategies used for communication in the website of Leite Condensado Moça, a very famous brand of condensed milk in Brazil, by the perspective view of memory and oral speech. It articulates theories and concepts from Ecléa Bosi and Henri Bergson, regarding memory and oral speech, and from Javier Royo regarding digital design. Although it is not often taken into consideration in researches about communication, the investigation of the relationship between memory and advertisement speech seems to be a very productive field. It is related to oral speech, but above all, it instigates and provokes some of the consumers’ affective factors. Thus, it is possible to notice that the strategy of Leite Condensado Moça is opportune and relevant, as it brings the product to the quotidian life, not only regarding consumption but also the family and the individuals’ historical identity. In this way, collective and individual memories blend themselves, the same way as memory and communication may blend.
Keywords: Publicidade; Memória; Consumidor; Comunicação; Leite condensado; Communication; Advertising; Memory; CNPQ::CIENCIAS SOCIAIS APLICADAS